1985
DOI: 10.1029/gl012i006p00337
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of the Dunn Point Formation (Nova Scotia): High paleolatitudes for the Avalon Terrane in the Late Ordovician

Abstract: Volcanic flows of the Late Ordovician Dunn Point Formation contain a generally univectorial magnetization which passes the fold test. Its steep direction (D = 335°, I = −61°, k = 79, α95 = 4.2°, paleopole at 2°S, 136°E) is unlike any known for North America or for the Avalon terrane for post‐Ordovician time, so that a primary age of the magnetization appears to be very likely. The paleolatitude (42°S) for the Avalon terrane derived from this result is much higher than that predicted for the area on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 14 publications
5
18
0
Order By: Relevance
“…Paleocontinental reconstructions (Fig. 1) indicate that Avalonia was a microcontinent during most of the Ordovician, having separated from the northern Gondwanan margin by the Early Ordovician during the formation of the Rheic Ocean (e.g., van Staal et al 1998van Staal et al , 2009Sanchez-Garcia et al 2003;Murphy et al 2006). Avalonia's time as a microcontinent was terminated by its collision with Baltica in the Early Silurian and with Laurentia by the end of the Silurian (e.g., Fortey 1982, 1990;Keppie 1985;Van der Voo 1988;Murphy et al 1996aMurphy et al , 2006MacNiocaill et al 1997;van Staal et al 1998van Staal et al , 2009Cocks and Torsvik 2002).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Paleocontinental reconstructions (Fig. 1) indicate that Avalonia was a microcontinent during most of the Ordovician, having separated from the northern Gondwanan margin by the Early Ordovician during the formation of the Rheic Ocean (e.g., van Staal et al 1998van Staal et al , 2009Sanchez-Garcia et al 2003;Murphy et al 2006). Avalonia's time as a microcontinent was terminated by its collision with Baltica in the Early Silurian and with Laurentia by the end of the Silurian (e.g., Fortey 1982, 1990;Keppie 1985;Van der Voo 1988;Murphy et al 1996aMurphy et al , 2006MacNiocaill et al 1997;van Staal et al 1998van Staal et al , 2009Cocks and Torsvik 2002).…”
Section: Introductionmentioning
confidence: 96%
“…During the Ordovician, Avalonia separated the southern margin of the Iapetus Ocean from the northern margin of the Rheic Ocean (van Staal et al 1998(van Staal et al , 2009Murphy et al 2006) and its collision with Baltica resulted in the demise of the Tornquist Sea. Therefore, the Ordovician tectonic history of Avalonia has first-order implications for the evolution of the oceans and seas that border it, and the paleogeographic relationship between Laurentia, Baltica, and Gondwana.…”
Section: Introductionmentioning
confidence: 99%
“…The Avalon poles are widely.dispersed and no readily evident apparent polar wandering path (APWP) has yet been established. A post-Devonian sinistral displacement of "Acadia" relative to cratonic North America proposed by KENT andOPDYKE (1978, 1979) and VAN DER VOO et al (1979) is unsupported by recent paleomagnetic data IRVING and STRONG, 1985;KENT and OPDYKE, 1985). KENT (1982) proposed that the Avalon platform shared this hypothetical sinistral displacement; however, STRONG (1984a, b, 1985) have shown that the magnetizations used to document this displacement hypothesis were in fact Late Carboniferous-Permian overprints.…”
Section: Previous Paleomagneticstudies On the Avalon Zonementioning
confidence: 99%
“…Newer Avalonian results were obtained from Lower Ordovician red sandstones in Newfoundland (RAO, 1970;BUCHAN and HODYCH, 1982;OZDEMIR and DEUTSCH, 1984), SiluroDevonian gabbros (ROY et al, 1979) and sedimentary rocks (ROY and ANDERSON, 1981) from New Brunswick, from Carboniferous redbeds in New Brunswick (ROY andPARK, 1974), in Newfoundland (KENT, 1982) and in Nova Scotia (SCOTESE et al, 1984). Other Avalonian paleomagnetic data include the Cambrian to Devonian granitic intrusives from Cape Breton (RAO et al, 1981), the Siluro-Devonian mafic dykes (SEQUIN et al, 1982a) from Newfoundland, the Early Silurian Dunn Point volcanics ( VAN DER VOO and JOHNSON, 1985) from Nova Scotia and Upper Hadrynian as well as Late Devonian rock formations from the Burin Peninsula (IRVING and STRONG, 1985) in Newfoundland. A summary of all these paleomagnetic poles is presented in Table 2 of the study of Early Cambrian redbeds (RAO et al, 1986) from Cape Breton.…”
Section: Previous Paleomagneticstudies On the Avalon Zonementioning
confidence: 99%
“…530 Ma poles for Laurentia and Gondwana are also used for 530-550 Ma, whereas, the 550 Ma pole for Baltica is the f-corrected pole of Meert (2013) who corrected for inclination shallowing in the Popov et al data (2005). Avalonia poles are from Pisarevsky et al (2008Pisarevsky et al ( , 2012, Thompson et al (2010aThompson et al ( , 2012, Johnson and Van der Voo (1985), and Van der Voo and Johnson (1985): the 490 Ma pole was also used for 500 Ma. Carolinia poles are from Vick et al (1987) and Noel et al (1988).…”
Section: -500 Ma (Late Ediacaranmiddle Cambrian) Reconstructionsmentioning
confidence: 99%